Performance Based Seismic Design Analysis of Steel Frames for Various types of Bracings: Evaluating the Performance of Steel Frames under Earthquake Loading (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In the recent earthquake, it is observed that losses are increased due to the seismic design of buildings using codal procedure is not able to achieve best performance during earthquake. The Civil Engineering profession has been changing the structural engineering design paradigm from life safety (LS) to Performance Based Seismic Design (PBSD) to tackle catastrophic damage caused by recent earthquakes worldwide. This paper is about the PBSD analysis of steel frame subjected to earthquake loading. Steel is by far the most versatile building material in the world and steel structure has played a major role in construction industry in the last decades. In this a multistoried bare and braced steel frames are analyzed by PBSD procedure in STAAD Pro Advanced following nonlinear static analysis. Frame components (beam, columns, etc.) are progressively adjusted to account for nonlinear elastic–plastic behavior under constant gravity loads and incrementally increasing lateral loads. Capacity curve is obtained for each frame and comparatively studied to decide which type of frame can meet the desired performance level during earthquake. The results of the analysis performed to meet required performance are presented in terms of displacement, shear forces, plastic hinges and capacity curve.